A Percolation-Based Model Explaining Delayed Take-Off in New-Product Diffusion - Martin Hohnisch; Sabine Pittnauer; Dietrich Stauffer (University of Bonn, Bonn Graduate School of Economics (BGSE), 2006)
A model of new-product diffusion is proposed in which a site-percolation dynamics represents socially-driven diffusion of knowledge about the product's characteristics in a population of potential buyers. A consumer buys the new product if her valuation of it is not below the price of the product announced by the firm in a given period. Our model attributes the empirical finding of a delayed ``take-off'' of a new product to a drift of the percolation dynamics from a non-percolating regime to a percolating regime. This drift is caused by learning-effects lowering the price of the product, or by network-effects increasing its valuation by consumers, with an increasing number of buyers.
Keywords: L15; C15; O33; 330; new-product diffusion; innovation adoption; spatial stochastic processes; percolation